2001
DOI: 10.1002/1521-3765(20010518)7:10<2167::aid-chem2167>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Tl−Pt(CN)5 in the Solid State—A Multimethod Study of an Unusual Compound Containing Inorganic Wires

Abstract: The crystal and molecular structure of a polycrystalline powder with a metal-metal bond and the composition TlPt(CN)5 has been determined by combining results from X-ray powder diffraction (XRD), extended X-ray absorption fine structure (EXAFS) and vibrational spectroscopic studies. The XRD data gave the tetragonal space group P4/nmm (No. 129), with a= 7.647(3), c=8.049(3) A, Z=2, and well-determined positions of the heavy metal atoms. The Pt-TI bond length in the compound is 2.627(2) A. The platinum atom coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 47 publications
(34 reference statements)
1
49
1
Order By: Relevance
“…Preparations. Aqueous solutions of the complexes [Pt(CN) 5 (OH)] 2- and [Pt(CN) 5 (H 2 O)] - were obtained as described previously from redox decomposition of the solid TlPt(CN) 5 compound. , The [Pt 2 (CN) 10 ] 4- complex can be prepared in aqueous solution either from a redox reaction occurring between the [Tl III (CN) n ] 3- n and [Pt(CN) 4 ] 2- (in excess) complexes 15 or by photoredox decomposition of a trinuclear [(NC) 5 Pt−Tl−Pt(CN) 5 ] 3- complex in aqueous solution . The [Pt(CN) 5 I] 2- complex was prepared according to a procedure described in the literature .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparations. Aqueous solutions of the complexes [Pt(CN) 5 (OH)] 2- and [Pt(CN) 5 (H 2 O)] - were obtained as described previously from redox decomposition of the solid TlPt(CN) 5 compound. , The [Pt 2 (CN) 10 ] 4- complex can be prepared in aqueous solution either from a redox reaction occurring between the [Tl III (CN) n ] 3- n and [Pt(CN) 4 ] 2- (in excess) complexes 15 or by photoredox decomposition of a trinuclear [(NC) 5 Pt−Tl−Pt(CN) 5 ] 3- complex in aqueous solution . The [Pt(CN) 5 I] 2- complex was prepared according to a procedure described in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…Pt L III -edge EXAFS data were collected in transmission mode at the Stanford Synchrotron Radiation Laboratory (SSRL) at the experimental station 4-1. The experimental conditions were similar to those described previously. ,, The energy calibration was made by simultaneously scanning a Pt foil for which the first inflection point was set to 11 564 eV. In the samples containing thallium, the usable range for the Pt L III -edge EXAFS measurements is limited to k ≈15 Å -1 by the Tl L III -edge at 12 658 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound is stable to 520 ЊC! 170 Another equally amazing structure involves four bridging Tl() ions sandwiched by two tetraalkynylplatinate [Pt(CCR) 4 ] 2Ϫ fragments. Each Tl() was sited away from the Pt fragments and interacted asymmetrically with four alkynyl ligands, the bonding was described as {µ 3 -η 2 :σ-Pt:η 2 (Tl,Tl)}, forming an approximately square-pyramidal geometry with the TI at the apex.…”
Section: Thalliummentioning
confidence: 99%
“…If water is present the compound becomes Tl[Pt(CN) 5 (H 2 O)]. 179 In parallel work, using EXAFS methods on Tl()-Pt() cyanide complexes showed that the Pt-Tl bonds were about 262 pm long, while 13 C, 195 Pt and 203 Tl NMR spectra showed that a two-electron redox process to Pt() and Tl() occurred in solution with the Pt-Tl complexes as intermediates. 180 Further developments have come from the reactions of various Tl() complexes containing dmso and/or en with [Pt(CN) 4 ] 2Ϫ and cyanide to give such species as [(NC) 5 PtTl(en) 2 ] ϩ with direct Pt-Tl unsupported bonds that are also stable in solution.…”
Section: Platinum Simple and Coordination Compoundsmentioning
confidence: 99%